Physiological Changes Following Pollination of Dendrobium Pompadour Flowers - Yip Y. K, Zuliana R.';; 11, Nair,; A. N, Boyce,; S., Chandran (Malaysian Journal of Science, 2008)
One of the most astounding phenomena in many flower species is pollination-induced senescence, where longevity of long-lived flowers is reduced and the functional life of the flowers are terminated. Ethylene which has long been implicated as the precursor of this phenomenon signals for other accompanying physiological changes such as perianth closure, discolouration, petal thinning, loss in flower weight and water uptake. Dendrobium Pompadour is one such orchid that undergoes pollination-induced senescence. In this study, it was found that the longevity of Dendrobium Pompadour flowers was significantly reduced by pollination. Furthermore, the quality of pollinated flowers was also significantly reduced when compared to unpollinated Dendrobium Pompadour.